A prospective study of thyroid dysfunction in dysfunctional uterine bleeding - M., Chaithra; S., Anitha G.; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dysfunctional uterine bleeding is abnormal uterine bleeding in the absence of any palpable pelvic pathology and demonstrable extra genital causes. Thyroid dysfunction is the systemic disease most often associated with abnormal uterine bleeding. Aim was to evaluate thyroid function test in women with DUB; to assess bleeding pattern in thyroid dysfunction. Methods: Prospective observational study was done in the department of obstetrics and gynaecology, Vanivilas hospital, Bangalore from august 2018 to July 2019. Pre structured and predesigned proforma filled. All routine blood investigations including serum T3, T4, TSH, USG were advised. These patients were categorized as euthyroid, subclinical hypothyroid, hypothyroid or hyperthyroid based on thyroid profile. Results: 0.5% belonged to the age group of 31-40 years, prevalence of subclinical hypothyroidism is 11%, there were 5.5% of cases of hypothyroidism and 1.5% case of hyperthyroidism. Conclusions: Thyroid screening must be done mandatory for all the cases of DUB and prompt response to treatment with thyroxine would avoid unnecessary surgeries, hormonal treatment, and associated comorbities.